The Kidai Shōran scroll : - Ozawa, Hiromu (Japan Publishing Industry Foundation for Culture (JPIC), 2020)
The Kidai Shōran is a magnificent painted Japanese scroll, an artistic rendering of one of the most iconic streets of Edo at the beginning of the nineteenth century.